The Use of Bromeliads as Biomonitors of Air Quality: A Global Review - Ángel Benítez; Luis Montaño; Azlan Abas; Omar Cabrera; Esteban Torracchi-Carrasco (International Journal of Forestry Research)
Air pollution is a global problem in urban and rural areas, mainly related to vehicular traffic and industrial activities. Bromeliads have been widely used globally for active and passive air quality monitoring. However, a systematic review to facilitate the access and analysis of this information is yet to be made available. The objective of this work was to systematically review the use of bromeliads in biomonitoring of the air quality from articles published between 1990 and 2023 to analyze the progress and impact of the research related to the type of monitoring, species used, pollutants measured, and sampling protocols. The search was carried out in global (Scopus, ISI Web of Science, ScienceDirect, and MDPI) and regional (SciELO and Redalyc) databases with a total of 60 scientific articles, where the neotropical region with 31 articles and the Nearctic region with 11 articles were the most influential regions. In addition, more than 90% of the research has been published in high-impact journals (quartile 1). Passive monitoring registered 25 articles compared to active monitoring with 23, with 23 species of the family Bromeliaceae, predominantly the genus Tillandsia. Tillandsia usneoides was the most common species used in active monitoring, while Tillandsia recurvata was used for passive monitoring. The measurement of heavy metals was the preferred technique (93% of the studies) for air quality monitoring, where Zn, Fe, Pb, Cr, and Mn and the nonessential elements K, Ca, and Na were the most measured. Results obtained by different research groups cannot be compared directly because different methodologies have been used, highlighting the importance of standardized techniques for future work. Thus, as a contribution in this direction, we propose a protocol to facilitate or standardize the selection of the proper methodology for developing air quality monitoring using bromeliads.